Field notes contributed by Bruce Ehresman, summer 1997 - Ehresman, Bruceet al (1997)
Summer report of birds and locations contributed by Bruce Ehresman. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1997. Epson - sheet feed/flatbed